USULAN PENGEMBANGAN MIE SEDAAP UNTUK MENINGKATKAN MARKET SHARE BERDASARKAN CUSTOMER LOYALTY FACTORS - Amadio Noviandri, Wishnu
PT Wings Group is an Indonesian-household products company. One of the products giving a significant contribution to the company's revenue is Mie Sedaap. Currently, there is a significant increase in the demand for instant noodles in Indonesia. The market share of Mie Sedaap is still far below that of its main competitor, Indomie. Therefore, PT Wings Group strives to increase this market share. This study employs a sentiment analysis approach to address issues from online reviews and customer comments on social media related to customer disloyalty. Using online reviews can save cost and time compared to using questionnaires in understanding the asymmetric relationship between product quality attributes and customer satisfaction. A total of 445,623 online review data points were obtained from social media and e-commerce platforms. The data were then cleaned through several stages, resulting in 52,818 disloyalty data points. The cleaned data were extracted using latent Dirichlet allocation (LDA) and then qualitatively analyzed by area sales managers into twelve customer satisfaction dimensions (CSD). Those twelve CSD identified were variety, taste, spiciness level, promositions, texture, sauce/calories, availability, packaging, portion size, health, topping, and aroma. Each CSD was then classified based on asymmetric impact-performance analysis (AIPA) to understand the impact on overall customer satisfaction. Improvement priorities were determined based on Kano classification and importance-performance competitor analysis (IPCA). Results from AIPA calculation showed that spiciness level was categorized as excitement attribute, while other CSDs were categorized as basic attributes. Priorities were mapped based on Mie Sedaap's performance relative to Indomie, with respect to competitive advantages. The primary priorities for improving Mie Sedaap's product quality are increasing the spiciness level, enhancing product availability in various regions, and reducing the side effects perceived by customers when consuming the product. These three CSDs are categorized as "urgent actions" based on IPCA calculations.